The poetry of nature in the collection “Save Our Fish from Drowning” by the poet Raad Zamel - Dr. Husam Mohammed Dewan (Journal of College of Education, 2024)
Nature is a great source of inspiration for the poet; There is harmony and internal harmony between its elements, which makes it one of the most impressive and inspiring sources in the universe. Therefore, since its inception, poetry was linked to nature, and the poems carried many elements that could be symbols of different ideas and feelings: rain, rivers, mountains, and flowers, all of which could be symbols of life or death, love, sadness, or joy. The topic of nature is an essential part of poetry, with its impact on the senses and arousing a sense of beauty. This topic can contribute greatly to enriching the poem and making it carry deep and aesthetic messages.This study attempts to examine the poetry of nature in the poetry collection of the poet Raad Zamel (Save Our Fishes from Drowning), as nature in the collection constituted one of the most important components of the identity of the poetic text. The poet relied on nature in using images and symbols, conveying ideas and feelings, and conveying messages
Keywords: poetics, nature, Raad Zamel, natural image, natural symbol, natural paradox.